Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1528
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Referential and Non-referential It Using Gaze

Abstract: When processing a text, humans and machines must disambiguate between different uses of the pronoun it, including non-referential, nominal anaphoric or clause anaphoric ones. In this paper, we use eye-tracking data to learn how humans perform this disambiguation. We use this knowledge to improve the automatic classification of it. We show that by using gaze data and a POS-tagger we are able to significantly outperform a common baseline and classify between three categories of it with an accuracy comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…More recently, Loáiciga et al (2017) proposed a semi-supervised approach based on a combination of syntactic and semantic features for the classification of it. Yaneva et al (2018), on the other hand, report on experiments using features from eye gaze that prove to be more effective than any of the other types of features reported in previous works. This prior work points to the interest in understanding the behavior of pronouns like it, whose range of referential uses (entity, event, etc.)…”
Section: Computational Approachesmentioning
confidence: 95%
“…More recently, Loáiciga et al (2017) proposed a semi-supervised approach based on a combination of syntactic and semantic features for the classification of it. Yaneva et al (2018), on the other hand, report on experiments using features from eye gaze that prove to be more effective than any of the other types of features reported in previous works. This prior work points to the interest in understanding the behavior of pronouns like it, whose range of referential uses (entity, event, etc.)…”
Section: Computational Approachesmentioning
confidence: 95%
“…Other studies that use data from participants with confirmed diagnoses focus on readability research (Yaneva et al, 2017) and complex word identification (Štajner et al, 2017), including a survey on the text adaptation needs of adults with ASD (Yaneva et al, 2019) as well as an analysis of visual-semantic priming and narratives (Regneri et al, 2020). Yaneva et al (2016) publicly releases a multimodal dataset with text and eye-tracking data collected from adults with and without autism. Finally, among the papers that use data from participants with unverified diagnoses, one study focuses on topic modelling for an ASD support forum (Ji et al, 2014), while other studies focus on text simplification or reading assistance without reporting evaluation with ASD participants (Barbu et al, 2013;Evans et al, 2014).…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…This hypothesis has initiated a large body of psycholinguistic research that shows a relationship between text processing and gaze behaviour. Yaneva et al (2020) discuss the use of gaze features for the task of anaphora resolution. Their findings show that gaze data can substitute the classical text processing approaches along with the fact that human disambiguation process overlaps with the information carried in linguistic features.…”
Section: Related Workmentioning
confidence: 99%